Epidemiological Analysis of Stunting Incidence in Toddlers Based on Family Socioeconomic and Nutritional Factors in Indonesia - Achmad Hilal; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2025)
Stunting is a chronic nutritional problem that remains a public health challenge in Indonesia. This study aims to analyze the relationship between socioeconomic factors and family nutrition on the incidence of stunting in toddlers. This study design is an observational analytic with a cross-sectional approach, using simulated hypothetical data from 500 households with toddlers aged 24–59 months. Bivariate analysis was conducted using the chi-square test, while multivariate analysis used multiple logistic regression. The simulation results show that the most influential factors on the incidence of stunting are maternal education level (p<0.01), family income (p<0.05), and toddler energy-protein intake (p<0.01). Toddlers from families with low socioeconomic status have a 3.5 times higher risk of stunting than families with middle to upper economic status. The conclusion of this study is that socioeconomic determinants and family nutrition play an important role in determining the nutritional status of toddlers in Indonesia. Prevention efforts need to be directed at improving nutritional education and family economic empowerment.